2000
DOI: 10.1007/s003300050969
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative embolization of bone metastases from renal cell carcinoma

Abstract: The purpose of this study was to correlate the effectiveness of preoperative embolization with the blood loss and transfusion requirement during surgery for bone metastases from renal cell carcinoma. Twenty-eight preoperative embolizations in 26 patients with renal cell carcinoma metastatic to bone were retrospectively evaluated and divided into two groups: Group A included the embolizations that resulted in complete devascularization of the lesion as defined by the post-embolization arteriograms, and group B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 10 publications
2
71
1
4
Order By: Relevance
“…No agreement exists on the effect of degree of devascularization on estimated blood loss. Some authors suggest that tumor devascularization reduces estimated blood loss [2,4,6,16]; however, some have found no correlation between tumor devascularization and estimated blood loss [7]. In our study, we found no correlation between degree of devascularization and estimated blood loss.…”
Section: Discussioncontrasting
confidence: 93%
“…No agreement exists on the effect of degree of devascularization on estimated blood loss. Some authors suggest that tumor devascularization reduces estimated blood loss [2,4,6,16]; however, some have found no correlation between tumor devascularization and estimated blood loss [7]. In our study, we found no correlation between degree of devascularization and estimated blood loss.…”
Section: Discussioncontrasting
confidence: 93%
“…In contrast, as reported by the previous studies where TAE was performed, spinal column was the most common sites and most of these tumors were metas tatic in nature than primary bone tumor [15,16,19,22,28,29] . Retrospective study done by Radeleff et al [17] studied four metastatic lower limb tumors and five metastatic upper limb tumors out of 31 patients.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly 23 patients (82%) of our control group had GCT. None of the previous studies from literature comprised of this number of GCT and the most common histology in previous studies was metastatic tumors [16,19,21,22] . In a prospective study done by Lee et al [13] total 6 patients were studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embolisation is useful in (1) treatment of vertebral haemangiomas, 1 (2) palliative treatment of bone pain in metastases, 2 (3) reduction of intra-operative blood loss in bone metastases from renal cell carcinoma, 3,4 and (4) treatment of vertebral metastases. 5,6 Preoperative embolisation of benign lesions in the spine and sacrum is reported to reduce blood loss, aid surgery, and act as a primary treatment modality.…”
Section: Introductionmentioning
confidence: 99%